002 Persistent improvement in door-to-needle times after implementation of the helsinki protocol for routine acute stroke care. Issue 6 (24th May 2018) - Silsby, Matthew; Duma, Stephen R; Fois, Alessandro F; Koryzna, Joanna; Mahant, Neil; Evans, Andrew; Fung, Victor SC
Abstract : Introduction: Intravenous thrombolysis for acute ischaemic stroke is a time-critical intervention. Time to treatment may be reduced by implementing measures known as the Helsinki protocol. We aimed to investigate the effectiveness of implementing the Helsinki protocol at a large tertiary teaching hospital. Methods: The protocol for treatment of acute stroke at Westmead hospital was modified to mirror the Helsinki protocol. Focus was placed on reducing time factors after patient arrival to hospital, without changes to the existing infrastructure. This included: education of triage staff to improve stroke recognition; transferring patients directly from the ambulance to CT; intravenous contrast administration as standard CT imaging; and tissue plasminogen activator preparation in CT. The primary endpoints were 'door-to-CT' time (DCT) and 'door-to-needle' time (DNT). Results: Data from stroke calls made in-hours were compared from 2016–2017. In the 12 months prior to implementation, 156 stroke calls occurred and 26 patients received thrombolysis. In the initial ten-week study, 49 stroke calls occurred and seven patients received thrombolysis. Median DNT was significantly reduced (77.5 vs 28 min, p=0.0477). In the following six months, 93 stroke calls occurred and eight patients received thrombolysis. Median DNT remained significantly reduced (77.5 vs 39 min, p=0.012). DCT was unchanged across the eight-month period (26 vs 23 min, p=0.646). Post-implementation, fewer patients received thrombolysis (17% vs 11%), but the number of calls increased (13 vs 18 per month). Conclusion: Introduction of the Helsinki protocol for acute stroke calls resulted in a significant reduction in DNT. The changes persisted notwithstanding routine changes in junior staff. Fewer patients received thrombolysis, despite the focus on minimising delays. This might be because there were more calls, reflecting the preference for sensitivity over specificity. Reduction in DNT has significant implications for patient recovery and the effects of simple process changes persist beyond a dedicated study period.